Integrasi Audit Trail dan Pengendalian Internal Terhadap Loyalitas Anggota Koperasi - Miko Tri Afandi; Intan Ayu; Ahmad Mishbahul Munir; Atikah Kusuma Wati (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze the role of integrating audit trails and internal controls in enhancing member loyalty in cooperatives through transparency and accountability. The research employs a descriptive qualitative method, with data collected through interviews and observations at KSPP Syariah Mawar Simo Sungelebak Lamongan. The results indicate that the implementation of the SIBMT (Integrated Management-Based Information System) with audit trail features enables transparent and verifiable transaction records, thereby strengthening member trust. Effective internal controls, such as monthly audits and routine evaluations, minimize errors and fraud. The main challenge is human error in system operation, which can be mitigated through employee training. High member trust, active participation in meetings, and open financial reporting in the Annual Member Meeting (RAT) are key drivers of loyalty. The study concludes that the integration of audit trails and internal controls fosters transparent and accountable cooperative governance, ultimately boosting member loyalty.